Science fairs as learning tools - Esteves, Zita (2010)
Science fairs are activities well known, in different countries, for their pedagogical relevance. For that reason a 4 years study was developed to evaluate the advantages of this informal teaching method in the context of a basic school in the northwestern Portuguese seaside town of Viana do Castelo. The study included the analysis of the evolution of students that have participated in previous fairs, and also students participating in the present science fair. The motivation of the students was monitored and also the knowledge and skills’ gains achieved. This way, the relevance of this teaching modality is once more demonstrated, not only in what concern the short term, right after student participation, but also the students future attitude towards the school and their motivation to the study of science, as well as in long term knowledge and skills acquisition.